2009
DOI: 10.1016/j.amepre.2009.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Pounds Off Digitally Study

Abstract: Background As obesity rates rise, new weight loss methods are needed. Little is known about the use of podcasting (audio files for a portable music player or computer) to promote weight loss, despite its growing popularity. Design A 12-week randomized controlled trial. Setting/Participants Overweight men and women (body mass index, 25–40 kg/m2) (n=78) in the Raleigh–Durham, NC area. Intervention In 2008, participants were randomly assigned to receive 24 episodes of a currently available weight loss podca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 22 publications
2
51
0
1
Order By: Relevance
“…Although researchers have investigated dietary self-monitoring as an adjunct or follow-up to a behavioral weight loss intervention [44] or used a smartphone app to enhance adherence to another intervention [45], this pilot trial has taken a minimal contact approach with no dietary advice at baseline. The weight loss seen in the smartphone arm is encouraging given that a minimal contact approach could be a cost-effective and wide-reaching strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Although researchers have investigated dietary self-monitoring as an adjunct or follow-up to a behavioral weight loss intervention [44] or used a smartphone app to enhance adherence to another intervention [45], this pilot trial has taken a minimal contact approach with no dietary advice at baseline. The weight loss seen in the smartphone arm is encouraging given that a minimal contact approach could be a cost-effective and wide-reaching strategy.…”
Section: Discussionmentioning
confidence: 99%
“…These measures have been used in previous work (Ko, Turner-McGrievy, & Campbell, 2013; G. Turner-McGrievy & Tate, 2011; G. M. Turner-McGrievy et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Participants also downloaded two 15-minute podcasts each week that have been used to assist with weight loss in previous studies (G. Turner-McGrievy & Tate, 2011; G. M. Turner-McGrievy et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Six of the trials found no weight loss differences at any follow-up [33, 37, 4042, 46], while 12 trials found significant differences at one or more assessment ([2932, 3436, 38, 39, 4345]; see Table 1). As for specific modalities, six of the 18 trials assessed phone-based treatment [3133, 35, 39, 40].…”
Section: Resultsmentioning
confidence: 99%
“…One found that 24 podcast episodes based on social cognitive theory yielded greater weight loss than basic, educational weight loss podcasts [45]. The second trial compared treatment delivered by podcast to treatment including podcasts plus self-monitoring (using an online app) and a social media component.…”
Section: Resultsmentioning
confidence: 99%